POLA PEMBIMBINGAN AKADEMIK DOSEN WALI SEBAGAI UPAYA EFEKTIVITAS MASA STUDI MAHASISWA - Fakhrur Saifudin, M (Graduate Program Magister Manajemen Pendidikan, 2018)
This study aimed at (1) describing the guidance of academic lecturers in PGSD FKIP UAD; (2) describing the effectiveness of lecturerâs guidance in improving the study period of PGSD FKIP UAD students. The research method used was mixed methods. Data collection techniques were conducted by interview, observation, questionnaire, and documentation. The results of this study indicate that academic guidance in Prodi PGSD FKIP UAD apply the guidance system with classical pattern, individual pattern, and digital pattern. The results showed that the pattern of coaching is done by combining the counseling patterns tailored to the conditions and situations of students. Based on the results of the analysis, the role of academic counselors in improving the study period of PGSD FKIP UAD students shows a significant role. This is indicated by 7% of respondents considered very important, 63% answered important, 21% important enough, and 9% answered is not important. Referring to these results, that the role of mentor is considered important to the continuity of student studies. Furthermore, counseling activities based on the results of the analysis show academic information activities (KRS) of 34%, 18% thesis consulting consultation, administrative consultation of 14%, and other consultations.